Recent trends in rubberized and non-rubberized ultra-high performance geopolymer concrete for sustainable construction: A review - Alshaeer Honin; Amran Mugahed; Rezzoug Aïssa; Murali Gunasekaran; Makul Natt; Al-Yaari Mohammed; Avudaiappan Siva; Maureira-Carsalade Nelson; Alluqmani Ayed Eid (Reviews on Advanced Materials Science)
The construction sector faces significant sustainability and environmental challenges due to the extensive use of conventional concrete. In this regard, ultra-high-performance geopolymer concrete (UHPGC) offers a promising alternative, featuring both rubberized and non-rubberized formulations with unique benefits. Rubberized UHPGC enhances ductility and resilience by incorporating recycled materials, while non-rubberized variants provide superior strength and durability. A comprehensive review is essential to enhance the understanding of UHPGC, evaluate its role in sustainable development, and guide future research and policy in the construction industry. This review article provides an innovative analysis of UHPGC, emphasizing its novel integration of geopolymer binders and the incorporation of recycled rubber particles to enhance mechanical and environmental performance. It examines the evolution, properties, and applications of both materials, highlighting their rapid setting times, improved workability, and reduced shrinkage. Moreover, it underscores their superior compressive, tensile, and flexural strengths, as well as enhanced energy absorption, ductility, fracture energy, and crack resistance, making them suitable for high-stress environments. This review suggests that using crumb rubber as a fine aggregate replacement in geopolymer concrete generally reduces compressive strength at higher levels. However, small additions, around 2%, may improve strength, highlighting the need for careful optimization to balance the performance and strength. The addition of steel and polypropylene fibers to UHPGC enhances flexural toughness and fracture energy. The integration of rubber particles into ultra-high-performance rubberized geopolymer concrete (UHPRGC) significantly enhances its ductility, toughness, and energy absorption, allowing the material to withstand higher strains and preventing brittle failure, making it ideal for high-performance applications. However, the inclusion of rubber compromises compressive strength because of inadequate interfacial adhesion, enhancements in surface treatment and the optimization of composite formulations can effectively overcome these challenges, and merging customized rubber proportions with advanced polymeric or fiber reinforcements maintains mechanical integrity while capitalizing on rubber’s elasticity, suggesting the necessity for ongoing investigation into microstructural optimization and long-term performance to thoroughly harness the sustainability and functionality of UHPRGC.